2020
DOI: 10.11606/s1518-8787.2020054002569
|View full text |Cite
|
Sign up to set email alerts
|

Existe desigualdade socioeconômica na multimorbidade entre adultos brasileiros?

Abstract: OBJETIVO: Avaliar a prevalência de multimorbidade e a associação desta com indicadores socioeconômicos entre adultos brasileiros. MÉTODOS: Estudo transversal que utilizou dados oriundos da Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos no Brasil, realizada entre 2013 e 2014. Multimorbidade foi definida como a coexistência, no mesmo indivíduo, de duas ou mais doenças crônicas, e é mensurada a partir de uma lista de 14 morbidades (autorrelato de diagnóstico médico na vida).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
4
0
6
Order By: Relevance
“…The dire c t relationship b e t we en age and multimorbidity of NCDs is well established in the literature 6,7,8,9,10,11,22,24,25,26,27,28,29,30,31 . The study by Violán et al 23 , in Spain, was the only one that reported a higher prevalence (60.5%) of multimorbidity among young adults (25-44 years) when compared with the elderly.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The dire c t relationship b e t we en age and multimorbidity of NCDs is well established in the literature 6,7,8,9,10,11,22,24,25,26,27,28,29,30,31 . The study by Violán et al 23 , in Spain, was the only one that reported a higher prevalence (60.5%) of multimorbidity among young adults (25-44 years) when compared with the elderly.…”
Section: Discussionmentioning
confidence: 98%
“…As for sociodemographic variables, this study identified a prevalence of 10.2% of concurrent NCDs in women and 8.9% in men. The scientific literature has reported that women have a higher prevalence of multimorbidity of NCD s 6,7,9,10,11,23,24,25,26,27,28,29,31 . The highest prevalence of concurrent NCDs in women was 74% 24 and the lowest was 4.5% 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This interrelation between factors can be corroborated by the study of Chen et al 8 which indicates that multimorbidity affects individuals with lower educational attainment more severely, with the negative impact on activities of daily living being about three times greater in individuals with lower educational attainment. Regarding education, it is recognized as a variable that consistently influences health-related aspects 7,[15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, social determinants have gained prominence in the literature in recent decades, given the need to address inequalities that affect access to the universal right to health 5 . Among these, one can cite education, the various conditions of access to health information, management of lifestyle habits, and self-care 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Corroborando com o exposto estudo realizado porCosta et al (2020) em revisão sistemática evidenciaram que baixa escolaridade estava associada a 64% mais chances de apresentarem multimorbidade. Porém, quando esses estudos foram agrupados de acordo com idade, a associação foi maior nas populações mais velhas.…”
unclassified